2020
DOI: 10.1042/bcj20190776
|View full text |Cite
|
Sign up to set email alerts
|

ShNPSN11, a vesicle-transport-related gene, confers disease resistance in tomato to Oidium neolycopersici

Abstract: Tomato powdery mildew, caused by Oidium neolycopersici, is a fungal disease that results in severe yield loss in infected plants. Herein, we describe the function of a class of proteins, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), which play a role in vesicle transport during defense signaling. To date, there have been no reports describing the function of tomato SNAREs during resistance signaling to powdery mildew. Using a combination of classical plant pathology-, genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…SNAREs were found to participate in plant development [ 1 , 3 , 29 ], abiotic stress [ 12 , 31 ], and pathogen resistance pathways [ 21 , 25 , 30 , 39 , 40 , 41 ]. Furthermore, MeJA, SA, and ABA were proved to regulate plant resistance to S. sclerotiorum [ 42 , 43 , 44 , 45 , 46 ] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SNAREs were found to participate in plant development [ 1 , 3 , 29 ], abiotic stress [ 12 , 31 ], and pathogen resistance pathways [ 21 , 25 , 30 , 39 , 40 , 41 ]. Furthermore, MeJA, SA, and ABA were proved to regulate plant resistance to S. sclerotiorum [ 42 , 43 , 44 , 45 , 46 ] .…”
Section: Resultsmentioning
confidence: 99%
“…At the whole-plant level, SNAREs are mainly activated in response to stresses such as drought/osmotic stress, high salinity, abscisic acid (ABA)-induced stress, and pathogen stimuli. For example, AtSYP121 is involved in ABA-dependent drought stress in tobacco and non-host resistance against powdery mildew as well as oomycete attack in A. thaliana [ 2 , 23 , 25 ]. As a paralog of AtSYP121, AtSYP122 is phosphorylated in response to the elicitor flagellin [ 26 ] and has redundant functions with AtSYP121 in plant immunity and general secretion events [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants, resistance to biotrophic pathogens, e.g., O. neolycopersici, is closely related to the H 2 O 2 accumulation and generation of HR triggered by the fungal haustoria [7]. In the study of tomato powdery mildew resistance, more HR and H 2 O 2 are found in resistant tomatoes, including wild tomato S. habrochaites G1.1560 and S. habrochaites LA1777, compared to the susceptible S. lycopersicum MM tomato cultivar [9,10,60]. If the generation of HR and H 2 O 2 is reduced, the resistance to biotrophic pathogens will be decreased [28,61].…”
Section: Discussionmentioning
confidence: 99%
“…tritici ( Pst ) hypha; this behavior may play a role in vesicle-mediated resistance to stripe rust ( Wang et al, 2014 ). ShNPSN11 in tomato is located at the PM and plays an important role in defense reactions to O. neolycopersici ( Lian et al, 2020 ). In Arabidopsis, AtSYP71 belongs to the Qc-SNARE family and localizes to the PM and the ER ( Suwastika et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%